Songs during the Canonization Mass of Blessed Kinga Chaired by Pope John Paul II in Stary Sącz (June 16, 1999) - Stanisław Garnczarski (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The 7th Pilgrimage of the Holy Father to Poland was a special time for the Tarnowski Church community, because during the pilgrimage John Paul II was to come to Stary Sącz to canonize Saint Kinga. An important element of any liturgical meeting are song sand liturgical music. The present study aims to show various aspects of preparations in the musical field, from the liturgical theme of the celebration, through the performers, to the planned repertoire of songs. The canonization of Saint Kinga decided the subject matter of the texts, the performers were joined by choirs and orchestras, while the repertoire consisted of songs in honor of Saint Kinga, Eucharistic songs intended for the common singing of the entire community and choral works with orchestra accompaniment. Its character emphasized the very festive mood of this feast of faith.